Key principles for effective marine governance, including lessons learned after decades of adaptive management in the Great Barrier Reef - Day, Jon C. (Frontiers in Marine Science, 2022)
This paper reviews the concept of governance in protected areas, providing details about nine key principles of governance as they relate to marine protected areas (MPAs). Following a theoretical description of each principle, real-world examples of the principles are presented from the Great Barrier Reef (GBR) Marine Park, where marine governance has evolved over 45 years as part of adaptive management. Examples of good governance in the GBR include the intergovernmental arrangements that enable both federal and state governments to co-operate effectively across adjoining marine jurisdictions. In addition, the application of multiple layers of management adds to an effective integrated approach, considered to be the most appropriate for managing a large MPA. The nine governance principles discussed in the paper are applicable to all MPAs, but how they are applied will vary in dissimilar settings because of differing environmental, social, economic, cultural, and political contexts - clearly, one size does not fit all. The analogy of the nine principles being part of an interlaced or woven ‘lattice’ is also introduced. Collectively the lattice is stronger than any individual principle, and together all principles contribute to the totality of effective governance. The paper provides information for those involved in MPA management who are keen to understand marine governance and how it might apply to their MPA, recognising there will be differences in how the principles will apply.